90 Developing Patient-Focused Outcomes for Routine Clinical Care in Glioma: A Synthesis of Qualitative Evidence from the COMBaT Study - Noreen Hopewell-Kelly; Vimeeka Raj Devarajan; Silvia Goss; Helen Bulbeck; Rhian Burke; Anthony Byrne; Andrew Carson-Stevens; Gwawr Evans; Cerys Harris; Cressida Lorimer; James Powell; Sarah Puntoni; et al. (Neuro-Oncology, 2026)
Abstract Introduction There is a critical need to identify and routinely measure the outcomes that matter most to people living with glioma. Care needs in this population are complex and variable, yet current clinical practice lacks consistent, systematic approaches to assessing them. This may limit timely symptom management, personalised treatment and improvements in quality-of-life. We present findings from the first stage of the COMBaT study, to develop a person-focused core outcome set for routine glioma care. Methods A qualitative synthesis of existing evidence on patient care was undertaken, including: 1) updated systematic review of qualitative studies; 2) secondary analysis of 19 interviews with adults living with glioma. These data inform a draft list of outcomes designed to reflect the care needs of people with glioma. Outcomes will be refined in collaboration with an advisory group, comprising people with lived experience, clinicians, allied health professionals, and NHS digital infrastructure representatives. Results Data extraction and synthesis of 50 full-text studies are underway. Secondary analysis of interview data is complete. Emerging domains for measurement include: Physical symptoms: seizures; fatigue; sensory changes; weakness; headaches; dexterity; pain; speech and language difficulties. Mental affect, behaviour: cognitive changes; emotional expression; personality changes; depression; anxiety. Social wellbeing: quality-of-life including sleep, energy levels and weight changes. These domains will be refined with the advisory group ahead of systematic prioritisation in July 2026. Conclusions The qualitative synthesis will underpin a draft outcome set, to be prioritised using a modified Delphi process. Psychometric properties of existing patient-reported outcome measures will be mapped to the final set and ratified by stakeholders. The outputs will inform development of an implementation strategy to support consistent, person-focused outcome assessment in routine glioma care.